ANALISIS PENGARUH TATA KELOLA PERUSAHAAN TERHADAP EFISIENSI MANAJEMEN MODAL KERJA - Titis Muktiasih; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2019)
This study aims to examine the effect of corporate governance to working capital management efficiency. The independent variables of this study are CEO tenure, board size, audit committee and institutional ownership meanwhile, dependent variables are cash conversion cycle and current ratio. Control variable in this study is firm size. Population of this study are listed manufacturing companies in Indonesia Stock Exchange (IDX) in 2016-2017. This study used systematic random sampling method, with 77 total observation of samples. The observation in this study uses secondary data from financial statements and annual reports.of manufacturing companies. The analytical method used in this study is multiple regression analysis. The results of regression analysis showed that the CEO tenure and institutional ownership can improves working capital management efficiency through a faster cash conversion cycle. This results were also showed that the board size of commisioner and institutional ownership can improves working capital management efficiency through greater current ratio, while the audit committee does not affect working capital management efficiency.